Measuring Worker Perception on Remote Working Adoption During COVID-19 Pandemic: An Industrial Engineering Perspective: A Case Study in Indonesia for Identifying the Potential New Normal of Work Implementation - Tanika D Sofianti; Ivan Kurniawan; Aditya T Pratama; Jessica Florencia (The Indonesian Institute of Science and Technology Research, 2023)
The COVID-19 which started in late 2019 has led to extraordinary measures by government and commerce, to control and reduce the spread of the virus. Many companies have had to rethink the way they work due to travel restrictions and cancellations of major events. While workers related to production activities as well as system-related workers such as bank tellers, cashiers, medical staff, and distribution operators are still working on site, the majority of the workforce in Indonesia has been encouraged to practice